Characterization of the complete mitochondrial genome of the Libelloides sibiricus (Neuroptera, Ascalaphidae) - Qingbin Zhan; Yunpeng Gai; Yang Zhao (Mitochondrial DNA. Part B. Resources, 2024)
AbstractLibelloides sibiricus (Eversmann, 1850) is widely distributed in China, Korea and eastern Russia. To date, few studies have been conducted on this species, with the exception of morphological taxonomy studies. In this study, we sequenced the complete mitochondrial genome (mitogenome) of Libelloides sibiricus, which is 15,811 bp in length, with an overall A + T content of 74.8%, encoding 2 ribosomal RNA genes, 22 transfer RNA genes, 13 protein-coding genes, and a control region. The gene arrangement and components of L. sibiricus are identical to those of most other Neuropteran species. TAA is utilized as the termination codon for most PCGs and TAG for nd1, however, nd6 and atp6 used the incomplete termination codon TA- and cox1, cox2, nd5, cytb had termination codons consisting of only T–. In addition, we selected all known 59 species of Neuroptera from NCBI, and used Sialis hamata, Sialis melania, Sialis longidens and Sialis jiyuni (Megaloptera: Sialidae) as the outgroup. Phylogenetic analysis suggested that the mitogenome of L. sibiricus was the most closely related to L. macaronius and all the owlflies formed the monophyletic group within the superfamily Myrmeleontoidea.